Juglone induces apoptosis of tumor stem-like cells through ROS-p38 pathway in glioblastoma - Jinfeng Wu; Haibo Zhang; Yang Xu; Jingwen Zhang; Wei Zhu; Yi Zhang; Liang Chen; Wei Hua; Ying Mao (BMC Neurology, 2017)
Abstract Background Juglone is a natural pigment, which has cytotoxic effect against various human tumor cells. However, its cytotoxicity to glioma cells, especially to tumor stem-like cells (TSCs) has not been demonstrated. Methods TSCs of glioma were enriched from U87 and two primary cells (SHG62, and SHG66) using serum-free medium supplemented with growth factors, including bFGF, EGF and B27. After treatment of juglone with gradient concentrations (0, 10, 20, and 40 μM), the viability and apoptosis of TSCs were evaluated by WST-8 assay and flow cytometry. Reactive oxygen species (ROS) was labeled by the cell-permeable fluorescent probe and detected with flow cytometry. ROS scavenger (NAC) and p38-MAPK inhibitor (SB203580) were applied to resist the cytotoxic effect. Caspase 9 cleavage and p38 phosphorylation (P-p38) were quantified by western blot. Juglone as well as temozolomide (TMZ) were administrated in intracranial xenografts and MR scan was performed every week to evaluate the anti-tumor effect in vivo. Results Juglone could obviously inhibit the proliferation of TSCs in glioma by decreasing cell viability (P < 0.01) and inducing apoptosis (P < 0.01), which was accompanied by increased caspase 9 cleavage in a dose-dependent manner (P < 0.01). In the meantime, juglone could generate ROS significantly and increase p38 phosphorylation (P < 0.01). In addition, pretreatment with ROS scavenger or p38-MAPK inhibitor could reverse juglone-induced cytotoxicity (P < 0.01). More importantly, juglone could also suppress tumor growth in vivo and improve the survival of U87-bearing mice compared with control (P < 0.05), although TMZ seemed to have better effect. Conclusions Juglone could inhibit the growth of TSCs in gliomas through the activation of ROS-p38-MAPK pathway in vitro, and the anti-glioma effect was validated in vivo, which offers a potential therapeutic agent to gliomas.